"La hernia discal como enfermedad profesional en la policií nacional del Ecuador, distrito Quevedo" - Suárez Toro, Jimmy Diego (2017)
The subject under in this research proyect is the herniated disc as a disease that is acquired to consequence of expusere to factore ergonomics presents at the jobs of Ecuador National Police. The work was carried out in the comunity suveillance Unit of the Quevedo district............................................